Discourse theory and cultural analysis : media, arts and literature - Carpentier, Nico.; Spinoy, Erik. (Cresskill, NJ : Hampton Press, 2008)
INHOUDSOPGAVE [COPAC]##Introduction: From the Political to the Cultural, Nico Carpentier and Erik Spinoy##MEDIA##Dichotomized Media Discourses of the War: The Construction of Self and the Enemy in the 2003 Iraq War, Nico Carpentier##Reading the New Horizon: The Role of Romanian Discourse in the 2004 Elections Power Shift, Henrietta Anisoara Serban##Embedded Identity Building in Chinese/Taiwanese English-Language Press Narratives, Lut Lams## ARTS/FILM##The Changing National Identity in Contemporary Mexican Cinema, Garman Martinez##Antagonism and Genre: Resistance, the Costume Romance, and the Ghost of Greek Communism, N.Y. Potamitis##Chilean Traumatized Identity: Discourse Theory and the Analysis of Visual Arts, Hernan Cuevas Valenzuela##ADS##A Discursive Style of "McJob": Putting Laclau, Mouffe and Bakhtin to Work, David M. Boje and Yue Cai##Deconstructing a Portuguese City: Cement, Advertising, and the Hegemony of "Green Growth", Anabela Carvalho##ICT##An(other) Enemy: The Representation of Otherness in Videogame Culture, Evangelos Intzides and George Prevedourakis##The "Outside" Inside Us: Antagonisms and Identities in Taiwanese Online Gay Forums, Yow-Juin Wang##Downloading as Piracy: Discourse and the Political Economy of the Recording Industry, Benjamin de Cleen## LITERATURE##Agonism and Literary History, Stuart Sim##Literary Imaginaries: On Experiencing (In)determinancy in German Modernism, Sascha Bru##"These Really Incomprehensible Poems That Really Touch You": The Rise and Fall of the New Realist Discourse in Flemish Poetry, Erik Spinoy##Both Self and Other: The Construction of "Flanders" in National Socialist Literary Discourse, Ine Van Linthout. Author Index##Subject Index.
Met reg. en bibl. verwijzingen
boek